Arctic sea ice and freshwater sensitivity to the treatment of the atmosphere‐ice‐ocean surface layer. Issue 6 (18th June 2015) - Roy, François; Chevallier, Matthieu; Smith, Gregory C.; Dupont, Frédéric; Garric, Gilles; Lemieux, Jean‐François; Lu, Youyu; Davidson, Fraser
Abstract Global simulations are presented focusing on the atmosphere‐ice‐ocean (AIO) surface layer (SL) in the Arctic. Results are produced using an ocean model (NEMO) coupled to two different sea ice models: the Louvain‐La‐Neuve single‐category model (LIM2) and the Los Alamos multicategory model (CICE4). A more objective way to adjust the sea ice‐ocean drag is proposed compared to a coefficient tuning approach. The air‐ice drag is also adjusted to be more consistent with the atmospheric forcing data set. Improving the AIO SL treatment leads to more realistic results, having a significant impact on the sea ice volume trend, sea ice thickness, and the Arctic freshwater (FW) budget. The physical mechanisms explaining this sensitivity are studied. Improved sea ice drift speeds result in less sea ice accumulation in the Beaufort Sea, correcting a typical ice thickness bias. Sea ice thickness and drag parameters affect how atmospheric stress is transferred to the ocean, thereby influencing Ekman transport and FW retention in the Beaufort Gyre (BG). Increasing sea ice‐ocean roughness reduces sea ice growth in winter by reducing ice deformation and lead fractions in the BG. It also increases the total Arctic FW content by reducing sea ice export through Fram Strait. Similarly, increasing air‐ice roughness increases the total Arctic FW content by increasing FW retention in the BG.